Implementation of Guided Inquiry Based on Blended Learning to Improve Students’ Metacognitive Skills in Reaction Rate - Ulfa Nur Afifah; Utiya Azizah (International Journal of Chemistry Education Research, 2021)
The development of the educational paradigm in the 21st century emphasizes learning oriented to higher-order thinking skills, one of them is metacognitive skills. This study aims to improve the metacognitive skills of students through a guided inquiry learning model based on blended learning in reaction rate material. The research design used is One-Group Pretest-Posttest Design. The research was conducted in class XI MIPA 5 SMAN 2 Pamekasan. The data were obtained using the observation sheet instrument for the implementation of the learning model, the activities of the students, and the metacognitive skills test sheet. Data analysis was performed using the percentage, mean, n-gain, and paired t-test techniques. The results showed that 1) Guided inquiry learning model based on blended learning is carried out well with an average percentage of phase 1 of 94.88%, phase 2 of 100%, phase 3 of 97.92%, phase 4 of 98.44% and phase 5 of 96.88%, 2) The percentage of students' activities who are actively involved and relevant to guided inquiry learning model based on blended learning is 87.41%, 3) The metacognitive skills of students have increased in terms of the n-gain range, namely 0.53 - 0.62 with the medium category, dan 4) there is a significant difference in the results of metacognitive skills between before and after being given a guided inquiry learning model based on blended learning. The results showed that the guided inquiry learning model based on blended learning was effective in improving students' metacognitive skills